1993
DOI: 10.1029/92wr02986
|View full text |Cite
|
Sign up to set email alerts
|

MS‐2 and poliovirus transport in porous media: Hydrophobic effects and chemical perturbations

Abstract: In a series of p H 7 continuous-flow column experiments, removal of the bacteriophage MS-2 by attachment to silica beads had a strong, systematic dependence on the amount of hydrophobic surface present on the beads. With no hydrophobic surface, removal of phage at p H 5 was much greater than at pH 7. Release of attached phage at both pH values did occur, but was slow; breakthrough curves exhibited tailing. Poliovirus attached to silica beads at pH 5.5 much more than at pH 7.0, and attachment was also slowly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
97
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 22 publications
8
97
3
Order By: Relevance
“…Because quartz sand is negatively charged in source water (IEP = ~2.2), and MS2 is more negatively charged than phiX-174, MS2 experiences higher repulsion at pH = 7. Bales et al [56,57] also demonstrated that phiX-174 and poliovirus exhibit similar removal through sand columns due to their shared IEP of 6.6.…”
Section: Chapter 4 Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because quartz sand is negatively charged in source water (IEP = ~2.2), and MS2 is more negatively charged than phiX-174, MS2 experiences higher repulsion at pH = 7. Bales et al [56,57] also demonstrated that phiX-174 and poliovirus exhibit similar removal through sand columns due to their shared IEP of 6.6.…”
Section: Chapter 4 Discussionmentioning
confidence: 97%
“…Additionally, Bales et al [57] showed that poliovirus sorbed to silica beads much more readily than MS2. Small-scale studies with sand columns have also shown higher adsorption of rotavirus (IEP = 4.5) than MS2 [29].…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
“…From this body of work, it is known that factors influencing viral adsorption encompass characteristics of the soil solution, including ionic strength and composition (36,47,66), pH (38), and presence of dissolved organic matter (46); characteristics of the virus, such as isoelectric point (16,23) and hydrophobicity (9); and soil features, such as water content (33), clay and organic matter contents (40), and the presence of organic coatings (65). These findings have been extremely important in understanding the complex interactions between viruses and soil surfaces and in devising means of detecting viruses in soil.…”
mentioning
confidence: 99%
“…Previous investigations have examined the influence of soil and sediment physical characteristics on the extraction and cultivation of enteric and pathogenic viruses (2,23,45). Burgeoning interest in the role of viruses within soil and sediment microbial communities demands that ever more precise methodologies for the direct enumeration of total viral particles in sediments (12,13,28) and soils be developed (53).…”
mentioning
confidence: 99%